Effects of heat treatment on physicochemical and microstructure properties of myofibrillar proteins combined with glucose and cellulose nanofibers. (1st September 2022) - Wang, Peng; Li, Yan; Qu, Yujiao; Wang, Baowei; Huang, Ming; Sun, Jingxin; Zhang, Mingai; Huang, He; Zhang, Congxiang
Highlights: The physicocization and microstructure of MP at different temperatures were studied. The properties of glucose and cellulose nanofibers modified MP were investigated. Glc and CNFs influenced MP by hydrogen bonds and molecular steric hindrance. Glc and CNFs improved the thermal stability of MP at 80 °C and 100 °C. The interaction mechanism of Glc and CNFs on MP was preliminarily illustrated. Abstract: The effects of unheated, 80 °C, 100 °C, and 121 °C on the physicochemical and microstructural properties of myofibrillary protein (MP) supplemented with glucose (Glc) and cellulose nanofibers (CNFs) were studied. The results showed that Glc and CNFs cross-linked with MP through non-covalent bonds when unheated compared with the unheated MP group, which increased the particle size and surface hydrophobicity of MP, and changed the secondary structure. At 80 °C and 100 °C, the particle size and hydrophobicity of MP significantly increased. At 121 °C, the contents of leucine and lysine in MP decreased by 16.2% and 19.9%, respectively, however, both Glc and CNFs could prevent this decrease. Meanwhile, microscopic images showed that the dispersion of Glc-MP and CNFs-MP were more uniform than the MP groups. Compared with Glc-MP, CNFs-MP had more uniform particle size distribution and better thermal stability at high temperatures (121 °C).